The forgotten foundations of fundraising : practical advice and contrarian wisdom for nonprofit leaders - Beer, Jeremy, 1972-; Cain, Jeffrey J., 1965- (John Wiley & Sons, Inc., 2019)
An entertaining, informative, and eminently useful guide that draws on psychology, data, and real-world experience to explain what really drives successful fundraising. In The Forgotten Foundations of Fundraising, Jeremy Beer and Jeff Cain, cofounders of American Philanthropic, a leading consulting firm for nonprofit organizations, offer practical lessons and unconventional wisdom for both nonprofit leaders and novices in the art and science of raising money. Drawing upon a wealth of experience, deploying an army of anecdotes, and using eye-opening American Philanthropic survey data, the authors provide a brisk, irreverent, and supremely useful introduction to fundraising for charities and nonprofits. The book explains the hows and whys of a variety of fundraising techniques, from direct mail to planned giving programs. It explores the benefits and pitfalls of prospect research, the keys to donor retention, and the essential elements of a healthy nonprofit culture. It gives insightful advice on making personal meetings count, soliciting foundations, and training young fundraisers. And it does so with sprightly prose and sharp observations. You'll never read another fundraising book quite like this one. Expertly deflating the pretensions of those who would make fundraising a bureaucratic and esoteric profession, Beer and Cain elucidate the practical knowledge and relationship skills that still matter more than anything else. They make an impassioned plea for the importance of civil society to American democracy and build a compelling case for fundraising as an honorable component of a healthy civic culture. Philanthropy is not about bottom lines and return on investment-successful fundraisers provide a platform for donors to affirm their ideals, values, and morals. Fundraising is serious, but learning about it needn't be a chore. The Forgotten Foundations of Fundraising is at once eminently practical and absolutely delightful.